Charting Spiritual Care The Emerging Role of Chaplaincy Records in Global Health Care - Peng-Keller, Simon; Neuhold, David (Springer Nature, 2020)
This open access volume is the first academic book on the controversial issue of including spiritual care in integrated electronic medical records (EMR). Based on an international study group comprising researchers from Europe (The Netherlands, Belgium and Switzerland), the United States, Canada, and Australia, this edited collection provides an overview of different charting practices and experiences in various countries and healthcare contexts. Encompassing case studies and analyses of theological, ethical, legal, healthcare policy, and practical issues, the volume is a groundbreaking reference for future discussion, research, and strategic planning for inter- or multi-faith healthcare chaplains and other spiritual care providers involved in the new field of documenting spiritual care in EMR. Topics explored among the chapters include: Spiritual Care Charting/Documenting/Recording/Assessment Charting Spiritual Care: Psychiatric and Psychotherapeutic Aspects Palliative Chaplain Spiritual Assessment Progress Notes Charting Spiritual Care: Ethical Perspectives Charting Spiritual Care in Digital Health: Analyses and Perspectives Charting Spiritual Care: The Emerging Role of Chaplaincy Records in Global Health Care is an essential resource for researchers in interprofessional spiritual care and healthcare chaplaincy, healthcare chaplains and other spiritual caregivers (nurses, physicians, psychologists, etc.), practical theologians and health ethicists, and church and denominational representatives.